Emotional Intelligence and Burnout of Teachers of Higher Education Institutions - Bocheliuk, Vitalii Y.; Shcherbyna, Serhiy S.; Turubarova, Anastasiia V.; Antonenko, Iryna Yu.; Rukolyanska, Nataliya V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Emotional intelligence is an important resource for overcoming professional stress in members of socionomic professions. The research objective is to determine the role of its components in the development of emotional burnout. A natural experiment was conducted, which determined the manifestations of emotional burnout of 56 university teachers at the end of the academic year. The author used the questionnaire. Two experimental groups were identified in the general sample: teachers with burnout and those resistant to burnout (16 and 30 people, respectively). At the end of the academic year, signs of burnout were detected in one-third of university teachers. The leading symptoms are emotional exhaustion and depersonalisation, with no reduction in professional achievement. The dynamics of emotional life during the annual professional cycle are shown. The integrated indicator of emotional intelligence (EI) remains at the same level, but there are structural changes in the components of intrapersonal intelligence. At the end of the year, teachers’ attention to their emotional states, work roles, and communication increase significantly. At the same time, there is a decrease in the ability to manage their own emotions. Resistance to burnout is accompanied by a high ability to realise and control their own emotions with a relatively vague focus on the emotional states of others. It was concluded that individual components of EI (intrapersonal and interpersonal, understanding and management) have different effects on burnout symptoms.